PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN AKTIVITAS SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - F34211571, Murni; ., Syambasril; ., Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: In an effort to improve student learning activities , the learning process, especially science class VI Elementary School 36 Tengon Upas still found weaknesses in teaching and learning activities as follows : students are not active , less excited , bored, become preoccupied and not paying attention to explanations of teachers. The demonstration is a way of presenting learning materials in which the teacher or resource person / people intentionally displaying or demonstrating actions / steps . The process is accompanied by explanations , illustrations , and students necessary to observe carefully